EKSISTENSI INSTITUSI PEMASYARAKATAN DALAM MEWUJUDKAN REINTEGRASI SOSIAL KEPADA WARGA BINAAN PEMASYARAKATAN - Yulianto, Rama Fatahillah; Muhammad, Ali (Universitas Wiralodra, 2021)
The modern legal paradigm now has been echoed by all elements of law enforcement. Currently, there are laws that are just and bring benefits to the whole community. The existence of penitentiary facilities is increasingly needed, especially in terms of fostering or returning, penitentiary inmates (WBP) to become fully human beings. The purpose of correctional is social reintegration which is implemented by restoring the life relationship, life, and livelihood of the PAPs. Actors implementing law enforcement, stakeholders, and the community must work hand in hand in carrying out social reintegration. Because it takes alignment of the legal paradigm adopted. This study refer to the existence of penitentiary facilities in realizing social reintegration for PAPs. The author uses a qualitative research method with a literature study approach. Researchers collect data that is relevant to the topic or problem that is linear with this research. Information is obtained from scientific books, research reports, research journal articles, regulations, scientific papers, and other written sources. The results of the study reveal that the existence of correctional facilities is increasingly important, especially in carrying out social reintegration. Therefore, it is necessary to strengthen between law enforcement and still require collaboration and alignment of the paradigm adopted between a number of elements, both actors implementing law enforcement, stakeholders, and the society.